Evaluation of the Summer Overheating Phenomenon in Reinforced Concrete and Cross Laminated Timber Residential Buildings in the Cold and Severe Cold Regions of China - Haibo Guo; Lu Huang; Wenjie Song; Xinyue Wang; Hongnan Wang; Xinning Zhao (Energies, 2020)
As the climate changed in recent years, an increase in summer indoor temperatures in severe cold and cold regions of China has started to affect thermal comfort. However, the local design standard for energy efficiency does not recognize this phenomenon. This paper reports the potential overheating phenomenon in residential buildings and examines the rationale for the current thermal designs adopted in severe cold and cold regions of China. In this study, the two most commonly used building materials, reinforced concrete (RC) and cross laminated timber (CLT), are used separately in the design of an 18-story residential building envelope located in six different cities in the severe cold and cold regions. The energy consumption and indoor operative temperatures during the operation of these buildings are simulated using Integrated Environmental Solutions Virtual Environment (IES VE). The results demonstrate that both the RC and the CLT buildings experience varying degrees of overheating in any climate subregion. The CLT buildings have longer overheating hours compared to the RC buildings, especially in the cold regions. The results also indicate that for apartments on higher stories, the cooling energy consumption and indoor temperature also increase gradually. The research results suggest that the local design standard for energy efficiency needs to be adjusted by adding thermal design methods for summer to reduce the periods of overheating.